Exchange rate alignment and producer support estimates (PSEs) for India - Cheng, Fuzhi; Orden, David (Wiley, 2007)
This article examines the effects of exchange rate alignment during 1985–2002 on agricultural producer support estimates (PSEs) for India. Based on several time series techniques, the equilibrium exchange rate of the Indian rupee and the corresponding misalignment of the actual rate are estimated and applied to recent PSE calculations. Our results show that the exchange rate was substantially misaligned before a financial crisis and macroeconomic reform in the early 1990s, with subsequent indirect effects on the PSEs. We find a relatively high pass‐through of exchange rate movements to domestic agricultural prices, so that removal of the exchange rate misalignment would have improved incentives to Indian farmers during this period. More recently, this indirect exchange rate effect is smaller than the direct effect in the PSEs, indicating the dominance of sectoral‐specific policies over economy‐wide policies.